2011
DOI: 10.1016/j.anifeedsci.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of total tract digestibility and nitrogen balance between Cinta Senese and Large White pigs fed on different levels of dietary crude protein

Abstract: a b s t r a c tThe work aimed to study the digestive capacity and nitrogen balance of Cinta Senese pig fed diets with different crude protein (CP) content. Twelve castrated male pigs (6 Cinta Senese and 6 Large White), of the same body weight (on average 62.7 kg), were submitted to 8 subsequent trials of total tract digestibility and nitrogen balance. The pigs were kept in metabolism cages allowing collection of faeces samples and total urine. The diets, of exclusive vegetal origin, were formulated to contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Therefore, the CP level in the diet of weaned pigs has been suggested to be one of the main factors that affect their growth performance (Gallo et al, 2014), feed efficiency, and gastrointestinal health (Yin and Tan, 2010;Acciaioli et al, 2011). An increase in the entry of nutrients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CP level in the diet of weaned pigs has been suggested to be one of the main factors that affect their growth performance (Gallo et al, 2014), feed efficiency, and gastrointestinal health (Yin and Tan, 2010;Acciaioli et al, 2011). An increase in the entry of nutrients (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in dietary crude protein (CP) levels can reduce diarrhea and nitrogen (N) excretion and repair digestive and immune function by enhancing the gene expression levels of digestive enzymes and amino acid (AA) transporters in young pigs [4,6]. For weaned pigs, it has been suggested that the CP levels in their diets can be reduced by 2-3 points without affecting average daily gain (ADG) [4,6], feed efficiency, or gastrointestinal health when the diets are supplemented with AAs [7,8]. However, reductions exceeding 3 points have produced no effects on ADG, feed efficiency and the mRNA levels of digestive enzymes (including trypsinogen, chymotrypsin B, and dipeptidase-II and III) and AA transporters [2,4,[9][10][11][12][13], although these trends have not been observed in all studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in good accordance with the present study and may be used as explanation for the current results. Acciaioli et al (2011) reported a significant increase (P<0.01) in crude protein digestibility of pigs of the same age, but different breeds, parallel to the increase of the lysine level in the diet. These findings were in accordance with the results of the present N balance studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kass et al (1980) found a negative effect of increasing BW on digestive capacity. Freire et al (2000) and Acciaioli et al (2011) concluded that pigs are able to improve their digestive ability with increasing age. Longland et al (1994) stated that the immature gut micoflora in young pigs is responsible for the decreased apparent digestibility of some nutrients.…”
Section: Discussionmentioning
confidence: 99%